Reinterpreting Vernon Smith’s “Microeconomic Systems as an Experimental Science” as Model-View-Controller Software Architecture - Robert L. Mayo (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
Smith (1982) presented a model of microeconomic systems as information processing mechanisms consisting of an environment and set of institutions. As an information processing discipline, computer science has developed an analogous paradigm by dividing processing elements into functional units in Model-View-Controller software architecture. Comparison of these two models provides new perspectives on Smith’s microeconomic systems model and suggests an extension through the addition of an explicit information feedback mechanism.